Effects of sucrose ester on the kinetics of polymorphic transition in hydrogenated sunflower oil - Herrera, María Lidia (1996)
The effect of a commercial emulsifier, sucrose ester, on the crystallization kinetics of hydrogenated sunflowerseed oil was studied by means of an optical method. Induction times were measured for hydrogenated oil with the addition of 0.01, 0.05, and 0.1 wt% sucrose ester. This emulsifier delayed nucleation, thus affecting the formation of critical nuclei and prolonging induction times. Kinetics of the β’→β polymorphic transition was followed by X-ray diffractometry. Addition of the emulsifier delayed the appearance of the signal at 4.6 A. Moreover, longer times were needed to complete the transition. The kinetic model chosen to describe the transition process was based on the theory of Avrami. Avrami’s exponentn was approximately 1 in all cases. Then value was in agreement with the fact that only one β’ pattern was found. The β form could not be obtained directly from the melt, and it is unlikely that the β’→β transition occurred through a melt-mediated mechanism. Transition was hindered by the rigidity of the sucrose ester structure.